Islamic Education Model in The Establishment of Social Ethics - Irhas M. Tuhur; Suprapto Suprapto; Mohamad Abdun Nasir (Asian Journal of Social and Humanities, 2023)
This study aims to determine the model of Islamic education in the formation of social ethics. Data collection in the preparation of this article uses qualitative methods with literature research and content review approaches. The results of this study show that the appropriate and effective model of Islamic education in the formation of social ethics is education by applying methods of understanding, habituation, and example